VALIDITY AND PRACTICALITY OF THE PROJECT MODULE: INTEGRATING PARAMASAN DAYAK LOCAL WISDOM - Wardhani, Dyah Febria; Arisanty, Deasy; Nugroho, Agung; Utami, Umi Baroroh Lili (International Conference On Social Science Education, 2024)
This study evaluates the validity and practicality of the developed The Pancasila Student Profile Strengthening Project module, designed to support the implementation of the Pancasila Student Profile. The module's validity was assessed across three key aspects: presentation, content, and language, achieving an average score of 93.75%, which classifies it as "very valid." The presentation was systematic and well-organized, while the content was highly relevant to the themes and student needs, though some areas were flagged for further improvement. The language used in the module was also rated highly, characterized by its clarity and communicative style. Revisions were implemented based on initial feedback, including corrections of typographical errors, improvements to the title, and the addition of essential elements within the module. The practicality of the module was evaluated by facilitators, who gave it an average score of 98.33%, indicating its suitability and ease of use in educational settings. Facilitators noted an enhanced understanding of project activity implementation and observed increased student motivation. The module was praised for its clear structure, well-defined learning objectives, and strong contextual relevance, all of which contribute to fostering student creativity and independence. In conclusion, the developed The Pancasila Student Profile Strengthening Project module shows considerable promise in enriching student learning experiences and advancing the educational objectives of the independent curriculum.